Propuesta de aprovechamiento del pseudotallo o vástago de plátano para fabricar fibras textiles en Colombia. (2022)
The present research project focuses on the importance of reusing agro-industrial waste generated in banana crops, in order to reduce environmental impacts and the proliferation of pests and diseases that deteriorate the quality of the fruit. For this reason, a survey of the information was carried out to identify the different utilization practices that are made of this waste to produce by-products such as paper, tea bags, hats, purses, shoes, among others. Evidencing this variety of products made from banana fibers, the idea of making textile fibers that help mitigate the massive contaminations caused by the textile industry in the world is contemplated.